2017
DOI: 10.3399/bjgpopen17x100809
|View full text |Cite
|
Sign up to set email alerts
|

Primary care knowledge and beliefs about physical activity and health: a survey of primary healthcare team members

Abstract: BackgroundPhysical activity has numerous health benefits and the primary healthcare team are ideally suited to promote activity. The Royal College of General Practitioners (RCGP) has announced physical activity to be a clinical priority in the next few years. However little attention is given to this in medical training, with unclear levels of knowledge and confidence.AimTo explore the primary healthcare team knowledge of the benefits of physical activity in preventing and treating ill health.Design & settingQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 16 publications
2
38
0
1
Order By: Relevance
“…Selection bias is a commonly cited limitation within the PA counselling literature and it is possible that doctors who engage in regular PA and enthusiastic proponents of PA counselling were more motivated to participate in this study 22 24 35 38–41. Therefore, it is possible that the high level of enquiry regarding PA levels in patients and the reported level of PA counselling activities undertaken in clinical encounters may be an overestimation of the real levels in practice and perhaps, an underestimation of the barriers to undertaking such activities within the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection bias is a commonly cited limitation within the PA counselling literature and it is possible that doctors who engage in regular PA and enthusiastic proponents of PA counselling were more motivated to participate in this study 22 24 35 38–41. Therefore, it is possible that the high level of enquiry regarding PA levels in patients and the reported level of PA counselling activities undertaken in clinical encounters may be an overestimation of the real levels in practice and perhaps, an underestimation of the barriers to undertaking such activities within the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome variables—PA enquiries and counselling (proportion of doctors who reported enquiring about PA habits and the proportion who reported providing verbal or written advice or exercise prescriptions to their patients regarding PA) were examined using descriptive analyses, as well as recoded as dichotomous variables (‘PA enquiry: yes/no’ and ‘PA counselling: yes/no’). Analyses to compare PA counselling activities according to level of seniority were undertaken with participants divided into the two groups: ‘doctors who have completed specialist training’ (ie, consultants and GPs) and ‘doctors who have not completed specialist training’ (ie, non-consultant hospital doctors or NCHDs) as level of seniority has been shown to impact on PA counselling activities in previous studies 21–24…”
Section: Methodsmentioning
confidence: 99%
“…As part of this approach, healthcare services can play an important role by implementing systems for patient assessment and counselling, and by strengthening the provision of and access to opportunities and programmes that enable older adults to increase their levels of physical activity [ 7 ]. Healthcare professionals play a central role in the promotion of a variety of health behaviours and are ideally positioned to promote physical activity [ 8 ]. Evidence suggests that they can positively impact patient behaviour by routinely assessing physical activity levels and by using brief practical interventions (advice or counselling on how to initiate and maintain healthy behaviours) with links to community-based support for behaviour change [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that healthcare professionals instigate brief physical activity interventions opportunistically in a quarter of appropriate instances [ 9 ] and there is a disparity between the development of guidelines for physical activity and their dissemination and integration into routine clinical practice for many healthcare professionals [ 12 , 13 , 14 ]. Barriers to physical activity promotion have been reported by healthcare professionals, including lack of awareness, expertise, and lack of time and incentive [ 8 ]. It is unclear what level of knowledge around physical activity exists across a broad range of healthcare professionals on the island of Ireland, and to what extent physical activity promotion with older adults is involved in decision making in routine practice.…”
Section: Introductionmentioning
confidence: 99%
“… 25 In particular, female students were significantly more likely than males to identify depression and anxiety/stress, 25 which was also observed in our study, though not statistically significant. This may be due to the fact that as women have a higher lifetime prevalence of mood or anxiety disorders than men, 26 they may have a greater knowledge of self-management strategies including the practice of regular PA. Additionally, among health professionals, a prior investigation found that “reducing the risk of cardiovascular disease”, “an effective treatment for depression” and “can help treat type two diabetes” were correctly referred as benefits of regular PA. 27 However, there was also a proportion who agreed with fictitious statements that were included, such as regular PA “could reduce the risk of glaucoma” and that “the only benefit of regular PA is weight loss”. 27 This result is particularly relevant since health professionals have a key role in providing PA-related knowledge to patients and promoting regular PA.…”
Section: Discussionmentioning
confidence: 99%